2011
DOI: 10.1007/s00296-011-2173-7
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effectiveness of various treatment modalities in carpal tunnel syndrome by ultrasonography and comparing ultrasonographic findings with other outcomes

Abstract: The most effective treatment modality was P-CS according to ultrasonographic and other findings. Although there were inverse correlations between the CSA of MN and sensory and motor MN conduction velocity, no relationship was found between symptom severity, functional status and US findings or electrophysiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 13 publications
1
24
1
Order By: Relevance
“…Our results were compatible with Uzun’s findings in that the improved symptoms between groups did not correlate with the improvement of electrophysiological measurements. The discordance between symptoms and electrophysiological improvement was expected because routine electrophysiological studies examine mainly large myelinated fibers rather than small sensory fibers which may be responsible for some symptoms of CTS 39 . Indeed, the electrodiagnostic measurement has a limited role in predicting the therapeutic outcome for CTS after surgery and conservative treatment in previous studies 23, 4042 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results were compatible with Uzun’s findings in that the improved symptoms between groups did not correlate with the improvement of electrophysiological measurements. The discordance between symptoms and electrophysiological improvement was expected because routine electrophysiological studies examine mainly large myelinated fibers rather than small sensory fibers which may be responsible for some symptoms of CTS 39 . Indeed, the electrodiagnostic measurement has a limited role in predicting the therapeutic outcome for CTS after surgery and conservative treatment in previous studies 23, 4042 .…”
Section: Discussionmentioning
confidence: 99%
“…Twenty RCTs were identified which examined carpal tunnel syndrome [ 134 153 ] ( Fig 7 ). Seven studies were excluded from data extraction as they recruited participants with bilateral involvement [ 135 , 137 , 139 , 142 , 143 , 148 , 149 ], which has implications for statistical analysis [ 154 ]. Data was extracted from nine studies, with effect size calculations completed for eight studies ( S4 File ) and odds ratio calculations for three studies ( S5 File ).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors suggested a close relationship [26, 27], while others proposed the opposite [28]. However, these variations are expected considering that routine electrophysiological tests mainly examine large myelinated fibers rather than small sensory fibers that may be responsible for some symptoms of CTS [29]. In our study, change in SNCV of the median nerve does not support this relationship, although significant improvement of VAS and BCTQ scores, CSA of the median nerve, and finger pinch strength was observed in both groups.…”
Section: Discussionmentioning
confidence: 99%